Women's attitudes towards intimate partner violence in Guyana: a population-based studyResearch in context - Gary Joseph; Charles C. Branas; Sandra Rupnarain; Monica Riutort; Christopher N. Morrison (Elsevier, 2024)
Summary: Background: Intimate partner violence (IPV) against women is a global health issue and a breach of human rights. However, the literature lacks understanding of how socioeconomic and geographic disparities influence women's attitudes toward IPV in Guyana over time. This study aimed to assess trends in women's attitudes about IPV in Guyana. Methods: Data from three nationally representative surveys from 2009, 2014 to 2019 were analysed. The prevalence of women's attitudes about IPV was assessed, specifically in response to going out without telling their partners, neglecting their children, arguing with their partner, refusing sex with their partner, or burning food prepared for family meals. A series of stratified subgroup analyses were also completed. We assessed trends in IPV using the slope index of inequality (SII) and the concentration index of inequality (CIX). We used multilevel mixed-effects logistic regression to assess factors associated with women's attitudes justifying IPV. Findings: The prevalence of women's attitudes justifying IPV for any of the five reasons declined from 16.4% (95% CI: 15.1-17.8) in 2009 to 10.8% (95% CI: 9.7-12.0) in 2019. Marked geographic and socioeconomic inequalities were observed among subgroups. The SII for any of the five reasons decreased from −20.02 to −14.28, while the CIX remained constant over time. Key factors associated with women's attitudes about IPV were area of residence, sex of the household head, marital status, respondent's level of education, wealth index quintile, and the frequency of reading newspapers/magazines. Interpretation: From 2009 to 2019, Guyana was able to reduce women's attitudes justifying IPV against women by 34.1% and shortened subgroup inequalities. However, the prevalence remained high in 2019, with persisted inequalities among subgroups. Effective strategies, including the use of media to raise awareness, promotion of community-based approaches, and educational campaigns focusing on geographic and socioeconomic disparities, are essential for continuing to reduce the prevalence of IPV and associated inequalities. Funding: The study was funded in part by the National Institutes of Health, Fogarty International Center grant number D43TW012189.